Extra and Intracellular Synthesis of Nickel Oxide Nanoparticles Mediated by Dead Fungal Biomass - Salvadori, Marcia Regina; Ando, Rômulo Augusto; Oller Nascimento, Cláudio Augusto; Corrêa, Benedito (PloS one, 2015)
The use of dead biomass of the fungus Hypocrea lixii as a biological system is a new, effective and environmentally friendly bioprocess for the production and uptake of nickel oxide nanoparticles (NPs), which has become a promising field in nanobiotechnology. Dead biomass of the fungus was successfully used to convert nickel ions into nickel oxide NPs in aqueous solution. These NPs accumulated intracellularly and extracellularly on the cell wall surface through biosorption. The average size, morphology and location of the NPs were characterized by transmission electron microscopy, high-resolution transmission electron microscopy, scanning electron microscopy, and energy dispersive X-ray spectroscopy. The NPs were mainly spherical and extra and intracellular NPs had an average size of 3.8 nm and 1.25 nm, respectively. X-ray photoelectron spectroscopy analysis confirmed the formation of nickel oxide NPs. Infrared spectroscopy detected the presence of functional amide groups, which are probable involved in particle binding to the biomass. The production of the NPs by dead biomass was analyzed by determining physicochemical parameters and equilibrium concentrations. The present study opens new perspectives for the biosynthesis of nanomaterials, which could become a potential biosorbent for the removal of toxic metals from polluted sites.